2011
DOI: 10.1177/1756283x11410770
|View full text |Cite
|
Sign up to set email alerts
|

Novel cytokine signaling pathways in inflammatory bowel disease: insight into the dichotomous functions of IL-33 during chronic intestinal inflammation

Abstract: In 2010, four independent groups almost simultaneously reported the association of the novel interleukin-1 (IL-1) family member, IL-33, with inflammatory bowel disease (IBD). The findings were remarkably consistent and demonstrated that IL-33 is markedly upregulated in, and specific to, ulcerative colitis (UC). In addition, although a variety of gut-associated immune cell subsets express IL-33, the primary source appears to be the intestinal epithelium. IL-33's receptor, ST2, a formerly orphaned IL-1 receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 68 publications
4
40
0
Order By: Relevance
“…IL-33 is a key immune modulator in the gut mucosa and has been implicated in host protective immunity against enteric nematode infection and gut inflammatory pathologies such as ulcerative colitis (16,29,30). The present study demonstrated that IL-33 promotes potent type 2 immunity in the intestine.…”
Section: Discussionsupporting
confidence: 58%
“…IL-33 is a key immune modulator in the gut mucosa and has been implicated in host protective immunity against enteric nematode infection and gut inflammatory pathologies such as ulcerative colitis (16,29,30). The present study demonstrated that IL-33 promotes potent type 2 immunity in the intestine.…”
Section: Discussionsupporting
confidence: 58%
“…Expression of IL-33 and its receptor ST2 has been shown to be dysregulated in IBD patients (10,12,13,37). However, whether IL-33 plays a tissue-protective or pathologic role in the colonic intestinal mucosa during disease remains controversial (10,11,30,31,(37)(38)(39), and the cellular and molecular mechanisms acting downstream of IL-33 to regulate disease are poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether IL-33 plays a tissue-protective or pathologic role in the colonic intestinal mucosa during disease remains controversial (10,11,30,31,(37)(38)(39), and the cellular and molecular mechanisms acting downstream of IL-33 to regulate disease are poorly defined. Here we identify the ILC2-AREG-EGFR axis as one mechanism by which IL-33 orchestrates intestinal tissue protection, associated with promotion of AREG-dependent mucin production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, IL-33 reduces the development of atherosclerosis (17), attenuates sepsis (34) and allows susceptible mice to expel the parasite (35). Indeed, the IL-33/ST2 system also plays a dichotomous role in inflammatory bowel disease pathogenesis (36,37), and the exact role of this axis needs to be further defined. Here, we show that IL-33 was markedly increased in the mice with TNBS-induced colitis, which mimics human CD.…”
Section: Il-33 Induces Regulatory T Cells Bymentioning
confidence: 99%